Marked Rebound of Platelet Count in the Early Postpartum Period in a Patient with Essential Thrombocythemia - Yoshinori Hashimoto; Rina Hosoda; Hiromi Omura; Takayuki Tanaka (Case Reports in Hematology)
Essential thrombocythemia (ET) occurs predominantly in the elderly, but approximately 20% of patients are <40 years old. Unlike other myeloproliferative neoplasms, ET occurs more commonly in women. We encountered a 38-year-old women diagnosed with ET who exhibited elevated platelet count in early pregnancy. Her platelet count exceeded 1500 × 109/L by late pregnancy; interferon α was administered but failed to induce an adequate response. She underwent emergency cesarean delivery at 37 weeks of gestation. Although her platelet count was 1000 × 109/L immediately after delivery, it markedly increased to 3271 × 109/L approximately 2 weeks later. Cytoreductive therapy was resumed; the subsequent course was free from complications. Several review articles have indicated that because platelet counts of patients may again increase to the pregnancy level or rebound after delivery, cytoreductive therapy should be administered if necessary. However, there is insufficient information on when therapeutic interventions are necessary and how they should be performed. It remains unknown whether the platelet count will decrease after some time without treatment if it rebounds. We hope management guidelines will be established by collecting detailed data on the postpartum course as well as during pregnancy.